Pengaruh Knalpot Racing Pada Kendaraan Roda Dua Yang Bising Di Kota Bima - Surip, Surip; Hendra, Hendra; Junaidin, Junaidin; Asmiatiningsih, Sri; Muhamadong, Muhamadong (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
In the midst of a pluralistic community life as problems occur that require legal resolution, so that the settlement has certainty. The complexity of legal issues becomes very dilemmatic. Even the law lags far behind when compared to the current incidence of crimes and offenses. However, amid the complexity of violations and crimes today, the law must provide legal certainty and a sense of security in society. One of the violations that concerns violations of technical requirements and roadworthiness is the use of exhaust racing / not stanfdar which directly shows an attitude of not having traffic ethics, where the use of